Statistical Analysis of a Questionnaire-Based Survey for Assessing the Impact of Tai Ji on the World Health Organization Definitions Regarding Quality of Life (QoL) - Dimitris Tsolakidis; Despina Kakatsaki; Dimitris Glotsos (Engineering Proceedings, 2023)
In this study, the aim was to evaluate the impact of Tai Ji on perceived quality of life (QoL). To this end, an anonymous online questionnaire was designed, compatible with the guidelines of the WHO for the definition of QoL, on the Microsoft Forms platform, using multiple-choice questions, short text answers, and Likert-based scales. The questionnaire was made public to practitioners of the Flow Tai Ji Center in Greece. The results showed that Tai Ji greatly improved the overall QoL for most participants, with more than 80% positive opinions.